2 - Post-colonial African Economic Development in Historical Perspective - Hirsch, Alan; Lopes, Carlos (Africa Development, 2020)
Africa is frequently framed in a narrative that reduces or minimises its significance and achievements. We review geographical and historical perspectives of Africa and present data that provides Africa greater significance and allows us to consider post-colonial African economic achievements outside of a simplistic narrative. We argue that placing Africa in a fairer historical and geographical perspective allows for more coherent planning for Africa’s future development.